(untitled) (Social Science Review, 2025)
Scams are commonly taking place globally, and the consequences of such fraudulent activities take a toll on individual privacy and national security. Financial scams in Bangladesh are on the rise, as numerous financial institutions continue to exploit political power to siphon public money through deceit. Although limited preventive measures are in place, but realistic methods have yet to be employed to recover money from these scammers. In contrast, Singapore, despite being highly ranked in many global indexes, suffers from a variety of scams, including purchase scams, credit for sex, and internet romance scams. By analyzing the available literature and secondary sources, this study aims to conduct a comparative analysis of different types of scams and their preventive mechanisms in Bangladesh and Singapore. The study finds that both countries have strict implementations of laws to prevent online fraud. Still, each country suffers from numerous obstacles to eliminating such crimes. However, Bangladesh has yet to develop a rigorous control mechanism for such crime, whereas Singapore has been quite advanced in dealing with various patterns of scams through its community interventions. Data collection and analysis were conducted to understand the current situation of scams in Bangladesh and Singapore, and the review was undertaken by deploying qualitative methods. However, the study acts as a crucial starting point for formulating comprehensive policies to combat the rising threat of online scams in Bangladesh. It highlights the urgent need for Bangladesh to establish robust regulatory frameworks and promote community-driven initiatives, while also drawing inspiration from Singapore’s sophisticated and effective strategies for scam prevention as a model. By encouraging international partnerships, and emphasizing data-driven policymaking, both nations can work together to tackle the dynamic and continually evolving nature of online scams with greater efficacy. Social Science Review, Vol. 42(1), June 2025, pp. 45-62